Corporate charisma how to achieve world-class recognition by maximising your company's image, brands, and culture - Temporal, Paul; Alder, Harry (Piatkus, 1998)
This guide aims to demonstrate how to create sustainable competitive advantage, attract new customers and outlast competitors in business. Chapters include: vision, mission and values; the psychology of a company; creating corporate charisma; and commmunicating the personality.